2013
DOI: 10.1063/1.4803941
|View full text |Cite
|
Sign up to set email alerts
|

W-doping induced antiferroelectric to ferroelectric phase transition in PbZrO3 thin films prepared by chemical solution deposition

Abstract: We reported on W-doping induced antiferroelectric to ferroelectric phase transition in PbZrO3 (PZO) thin films prepared on Pt/Ti/SiO2/Si substrates by a chemical solution deposition method. The phase transition has been studied through polarization-electric field hysteresis loop, capacitance-voltage characteristic, and Raman scattering measurements. Suitable amount W-doping increased the saturated polarization of antiferroelectric W-doped PZO thin films, whereas the ferroelectric W-doped PZO thin films exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…The PbZrO 3 thin films were deposited on Pt(111)/Ti/SiO 2 /Si substrates. Sa et al [33] reported the W-doping induced antiferroelectric to ferroelectric phase transition in PbZrO 3 thin films prepared on Pt/Ti/SiO 2 /Si substrates. With increasing W-doping content, the orientation of the thin films changed from preffered (111) Cubic to complete (100) Cubic , due to W-doping induced lattice distortion.…”
Section: Introductionmentioning
confidence: 99%
“…The PbZrO 3 thin films were deposited on Pt(111)/Ti/SiO 2 /Si substrates. Sa et al [33] reported the W-doping induced antiferroelectric to ferroelectric phase transition in PbZrO 3 thin films prepared on Pt/Ti/SiO 2 /Si substrates. With increasing W-doping content, the orientation of the thin films changed from preffered (111) Cubic to complete (100) Cubic , due to W-doping induced lattice distortion.…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric constant and dielectric loss usually decrease with increasing the bias electric field for FE materials. 10,11 For AFE materials, however, they first increase before AFE-FE transition, and then decrease with further increasing the bias electric field. 11,12 So very interesting mixed behavior of FE-like and AFE-like tunable dielectric properties is expected for AgNbO 3 ceramics with FIE and its Ag(Nb 1Àx Ta x )O 3 analogues.…”
mentioning
confidence: 99%
“…Furthermore, for an AFE material, even when the electric field is lower than AFE-FE transition field and not high enough for observing the characteristic double hysteresis loop, AFE-induced dielectric tunability can already be distinguished by the increase in dielectric constant and dielectric loss with bias electric field. 11,12 This is believed to ease the polar order determination of Ag(Nb 1Àx Ta x )O 3 ceramics, for which extremely high electric field is needed in case of hysteresis loop measurement. Although the FE-like dielectric tunability of AgNbO 3 and Nb-rich Ag(Nb 1Àx Ta x )O 3 ceramics has already been reported, the highest bias electric field was only 10 kV/cm.…”
mentioning
confidence: 99%
See 2 more Smart Citations